A Review of Electronic Hand Hygiene Monitoring: Considerations for Hospital Management in Data Collection, Healthcare Worker Supervision, and Patient Perception. Issue 5 (September 2015) - McGuckin, Maryanne; Govednik, John
Abstract : EXECUTIVE SUMMARY : Healthcare‐associated infections (HAIs) in U.S. acute care hospitals lead to a burden of $96‐$147 billion annually on the U.S. health system and affect 1 in 20 hospital patients (Marchetti & Rossiter, 2013). Hospital managers are charged with reducing and eliminating HAIs to cut costs and improve patient outcomes. Healthcare worker (HCW) hand hygiene (HH) practice is the most effective means of preventing the spread of HAIs, but compliance is at or below 50% (McGuckin, Waterman, & Govednik, 2009 ). For managers to increase the frequency of HCW HH occurrences and improve the quality of HH performance, companies have introduced electronic technologies to assist managers in training, supervising, and gathering data in the patient care setting. Although these technologies offer valuable feedback regarding compliance, little is known in terms of capabilities in the clinical setting. Less is known about HCW or patient attitudes if the system allows feedback to be shared. Early‐adopting managers have begun to examine their experiences with HH technologies and publish their findings. We review peer‐reviewed research on infection prevention that focused on the capabilities of these electronic systems, as well as the related research on HCW and patient interactions with electronic HH systems. Research suggests that these systems are capable of collecting data, but the results are mixed regarding their impact on HH compliance, reducing HAIs, or both and their costs. Research also indicates that HCWs and patients may not regard the technology as positively as industry or healthcare managers may have intended. When considering the adoption of electronic HH monitoring systems, hospital administrators should proceed with caution.